The 5‐year follow‐up of a real‐world observational study of patients in the United Kingdom and Ireland receiving ibrutinib for relapsed/refractory mantle cell lymphoma. (23rd May 2020) - Tucker, David; Morley, Nick; MacLean, Peter; Vandenberghe, Elisabeth; Booth, Stephen; Parisi, Lori; Rule, Simon
Summary: This is a 5‐year real‐world study of 65 patients treated with ibrutinib for relapsed/refractory mantle cell lymphoma across the UK and Ireland. Ibrutinib was well tolerated with no fatal adverse events. The median progression‐free survival and overall survival (OS) was 12 and 18·5 months, respectively. Overall, 80% of patients discontinued treatment, predominantly for progressive disease. On discontinuation, 20% received alternative immunochemotherapy with a median OS of 24 months. Ibrutinib was used as a bridge to transplant in 8% (median OS not reached). These observations are comparable with trial outcomes with encouraging responses to immunochemotherapy at relapse.